2019
DOI: 10.3389/fimmu.2019.02286
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Immune Homeostasis in Human Dendritic Cells via Regulation of Autophagy and Apoptosis by Porphyromonas gingivalis

Abstract: As fundamental processes of immune homeostasis, autophagy, and apoptosis must be maintained to mitigate risk of chronic inflammation and autoimmune diseases. Periodontitis is a chronic inflammatory disease characterized by oral microbial dysbiosis, and dysregulation of dendritic cell (DC) and T cell responses. The aim of this study was to elucidate the underlying mechanisms by which the oral microbe Porphyromonas gingivalis (P. gingivalis) manipulates dendritic cell signaling to perturb both autophagy and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 70 publications
1
50
0
Order By: Relevance
“…The inhibition of apoptosis contributes to the chronicity of the periodontal disease by promoting the growth of other bacterial species ( Figure 6) [17,91]. The LPS of P. gingivalis activates caspase 11 dependent noncanonical inflammasome and initiates the process of pyroptosis and lytic cell death within the macrophages [135,[184][185][186][187][188]. P. gingivalis LPS, specifically the O-antigen region and HmuY is known to affect the 'viability and apoptosis of gingival epithelial cells' [54,62,155,[187][188][189][190].…”
Section: Inhibition Of Apoptosis Increased Oxidative Stress and Activmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition of apoptosis contributes to the chronicity of the periodontal disease by promoting the growth of other bacterial species ( Figure 6) [17,91]. The LPS of P. gingivalis activates caspase 11 dependent noncanonical inflammasome and initiates the process of pyroptosis and lytic cell death within the macrophages [135,[184][185][186][187][188]. P. gingivalis LPS, specifically the O-antigen region and HmuY is known to affect the 'viability and apoptosis of gingival epithelial cells' [54,62,155,[187][188][189][190].…”
Section: Inhibition Of Apoptosis Increased Oxidative Stress and Activmentioning
confidence: 99%
“…The results of their study showed that the minor (Mfa1) fimbriae of P. gingivalis induce Akt nuclear localization and activate the Akt/mTOR axis required for autophagosome formation and maturation [190]. P. gingivalis also increase the mitotic cell cycle and suppress apoptosis by inhibiting Janus A Kinase (JAK), Phosphoinositide 3 Kinase (PI3 K), Signal Transducer of Activation (STAT), alpha-serine /threonine-protein kinase (Akt) and purinoceptor (P2X7) pathways ( Figure 7) [91] Furthermore, P. gingivalis reduce the renewal capacity of cells and inhibit apoptosis by activating p38, mitogen-activated protein kinase (MAPK), and extracellular-signalregulated kinase (Erk1/2) pathways [184][185][186] The activation of p38, MAPK, and Erk1/2 pathways decrease the expression of cyclin D and inhibit cellular proliferation by arresting the cell cycle at the G1 phase [72,73]. Studies have confirmed the deregulation of apoptosis-related genes, such as Bax, Bcl2, Nlrp3, or Smad2, in the gingival tissues of patients with periodontitis [181,189] P. gingivalis has also confirmed to possess cellspecific modulation of apoptosis receptors and signaling pathways such as Apoptotic protease activating factor (APAF 1), B-cell lymphoma Associated X (Bax1) and Caspase and reduce B-cell lymphoma (BCL 2) in the epithelial cells and fibroblasts [184].…”
Section: Inhibition Of Apoptosis Increased Oxidative Stress and Activmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, phosphorylated FOXO1 (p-FOXO1) translocates from the nucleus to the cytoplasm, where it undergoes proteosomal degradation, leading to inhibition of apoptosis, as FOXO1 is an important transcription factor involved in the regulation of the expression levels of proapoptotic genes such as Bim. DC infection by P. gingivalis significantly increases level of expression of phosphorylated Akt (p-Akt), increases nuclear translocation of p-Akt and cytoplasmic translocation of p-FOXO1, and ultimately decreases the levels of expression of proapoptotic proteins and extends the survival of DCs [68]. Not only does P. gingivalis disrupt homeostatic apoptosis in DCs [51], but it also disrupts DCs homing to secondary lymphoid organs via reprograming chemokine receptors on DCs, leading to transferring the inflammation to vascular sites [34].…”
Section: Defective Apoptosis and Risk Of Autoimmunity And Microbial Dmentioning
confidence: 99%
“…In addition, blocking DC-SIGN by HIV glycoprotein 120 reduces P. gingivalis survival inside DCs, but the mechanism of this phenomenon was unclear [102]. A recent report revealed that inhibition of autophagy in DCs by P. gingivalis involves targeting the Akt-mTOR pathway, which is an important regulator of autophagy [68]. P. gingivalis infection increases expression of p-Akt Ser473, p-mTOR Ser2448, p-Raptor Ser792, and p-ULK1 Ser757, all of which are important elements in mTOR-dependent autophagy inhibition [68].…”
Section: Autophagy a Tool For Resistance Or Susceptibility To Infectionmentioning
confidence: 99%